Detection of chlamydial antibodies in women with pelvic inflammatory disease and infertility - Ramona Perhar; Shilpi Rawat; Ruchi Pandey (Barpeta Obstetrics and Gynaecological Society, 2020)
Objective: To detect the chlamydial antibodies in women with pelvic inflammatory disease (PID) and infertility. Method: This study was carried out on 72 patients suffering from pelvic inflammatory disease and/ or infertility who were admitted in the indoor wards and those attending the out patient department. Control group comprised of relatives of patients, nursing staff and other staff of the hospital who did not have any present or past history of PID or infertility. Result: IgG and IgA antibodies were detectable in 50% cases of PID while IgG alone were detectable in 75 % cases of PID. Compared with the control group, the differences was statistically significant (p value < 0.001). Statistically significant (p<0.001) chlamydial IgG antibodies among the infertile subjects with fallopian tube disorders was found compared to the infertile subjects with normal tubes. IgG antibodies Chlamydia were positive in 1:64 dilution in 75% cases of PID and IgA antibodies Chlamydia were positive in 1:16 dilution in 50% cases of PID. Assay for IgG in infertile women, 10 % cases were positive at 1:128 dilution. Ten (33.33%) cases of infertility were positive for IgA antibodies (1:16dilution). Results are statistically significant as compared to control group (p value <0.001). Conclusion: It appears that testing for IgG antibodies at a serum dilution of 1:64 and for IgA antibodies at a dilution of 1:16 by the IPA test comprises the best combination for the differentiation between the PID patients and apparently healthy controls, and it is suggested that this be used as a marker of active C. trachomatis infection.